Psicologia na educação superior: atuação profissional em uma Universidade Federal - PENHA, Grasyelle Cristina Ferraz Almeida (2022)
Higher Education is one of the emerging fields of professional activity in Psychology, and in this context, studies of Critical School/Educational Psychology predominate. In addition to teaching, federal universities have held public competitions for the position of psychologist, with generalist job descriptions, suggesting different possibilities of action in relation to the specialties of Psychology and the various programs, policies and services in Higher Education. Currently, 1,404 psychologists experience professional practice in federal universities across the country, including in this scenario Psychology professionals, who work on the various campuses of the Federal University of Maranhão (UFMA). The main objective was to analyze the role of Psychology in Higher Education with UFMA as an empirical field. The research is qualitative and descriptive in nature. The theoretical foundations were based on official documents and legislation, studies in Psychology and Higher Education and in School/Educational Psychology. Seven psychologists from different university campuses participated, through a questionnaire and an interview with open questions, the information being analyzed from the Discursive Textual Analysis (DTA). The results point to five emerging categories: 1) professional practices in the fields of Student Assistance and People Management; 2) formation and professional identification with the areas of specialization of Psychology; 3) institutional organization and the psychologist’s work; 4) conceptions and contributions of Psychology in Higher Education, and; 5) psychologist's work, pandemic and illness. Psychology services were highlighted in the scope of People Management and Student Assistance in the capital and in the interior of the state. On the countryside campuses, there is a combination of traditional and emerging professional practices in Student Assistance, with individual and collective actions aimed at students, in addition to some institutional actions. On the São Luís campus, traditional practices prevail with individual actions for students in Student Assistance and traditional and emerging practices in People Management, with individual and collective actions aimed at servers. In these two contexts, conceptions about professional performance and Psychology services converge to the fields of health and/or education. Continuing education is highlighted as important by the interviewees, as added to professional experiences, they guide the psychological practices in the institution. The results denote a diversity in professional practices, distinct between the campuses of the countryside and the campus of São Luís, in addition to a multifaceted professional identification, with a professional performance involving different areas of Psychology, converging on School/Educational Psychology, Clinical Psychology, Psychology of Health and Organizational and Work Psychology (POT). Such information reveals the difficulties of professionals in the face of the demands encountered and the need to better direct the entry into federal universities. It is hoped that other studies can expand this discussion.